Vulnerabilità, ospitalità e cura in contesti culturalmente diversi - André, João Maria (Filosofia, 2023)
After establishing a philosophical frame of reference, we begin by thinking about current responses to cultural diversity, in the context of vulnerability and the anthropological characteristics that arise from it. But a significant part of the situations of vulnerability in the contemporary world, the reality of cultural diversity resulting from displacement movements, the situation of ethnic minorities and some post-colonization phenomena place at the center of responses to the challenges of this multiculturality the concept of hospitality: this concept not only has an ethical and political scope but is also characterized by its epistemological dimension and its anthropological meaning. The ethics of care, consideration, solicitude and resonance are then proposed as the referential framework within which we can today think about the social and political demands of welcoming those who represent difference within our societies.